1998
DOI: 10.1046/j.1365-2826.1998.00662.x
|View full text |Cite
|
Sign up to set email alerts
|

Glutamatergic Synaptic Inputs to Mouse Supraoptic Neurons in Calcium‐Free Medium in vitro/e1

Abstract: The effects of Ca2+-free perfusion medium on excitatory postsynaptic currents (EPSCs) and potentials (EPSPs) were studied by whole-cell recordings from neurons of the supraoptic nucleus (SON) in trimmed slice preparations of mouse hypothalamus. EPSCs evoked with either focal stimulation to the SON or perfusion of slices with high K+-medium, spontaneous EPSCs (sEPSCs) and miniature EPSCs (mEPSCs) recorded from neurons of the SON were blocked by the glutamate receptor antagonist kynurenic acid (1 mM). While EPSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 19 publications
0
8
0
1
Order By: Relevance
“…The average amplitude of miniature spontaneous postsynaptic currents was 21.18±2.47 pA (peak value; n = 7 cells, 360 events analyzed). Representative trace and offline analysis results are shown in Figure S8A– F. The offline analysis revealed that recorded miniature spontaneous postsynaptic currents have the amplitude or kinetic parameters comparable to those of human neurons [26], [27], [28]. These results demonstrate that smNPC-derived neurons have acquired the electrical properties of excitable neurons and developed synaptic contacts between neurons.…”
Section: Resultsmentioning
confidence: 72%
“…The average amplitude of miniature spontaneous postsynaptic currents was 21.18±2.47 pA (peak value; n = 7 cells, 360 events analyzed). Representative trace and offline analysis results are shown in Figure S8A– F. The offline analysis revealed that recorded miniature spontaneous postsynaptic currents have the amplitude or kinetic parameters comparable to those of human neurons [26], [27], [28]. These results demonstrate that smNPC-derived neurons have acquired the electrical properties of excitable neurons and developed synaptic contacts between neurons.…”
Section: Resultsmentioning
confidence: 72%
“…The advantage of this strategy is that by examining changes in the amplitude distributions of sEPSCs or mEPSCs it is possible to determine whether changes in synaptic efficacy occur at all synapses or whether these changes are limited to a subset of synapses (Turrigiano et al, 1998). Under control recording conditions sEPSCs and mEPSCs recorded from MNCs are equivalent; both arise from the activation of postsynaptic AMPA/KA receptors as they are completely blocked by DNQX (1 μM), and both represent the stochastic release of glutamate-filled vesicles as TTX has no effect on sEPSC frequency or amplitude (Gordon and Bains, 2003;Inenaga et al, 1998). Here, we refer to both sEPSC and mEPSCs as ‘quantal’ glutamate neurotransmission.…”
Section: Resultsmentioning
confidence: 99%
“…First, the -opioid receptor agonist, U69593, produces a large reduction in the frequency of both asynchronous release events and mEPSCs but has no effect on their mean amplitude. Second, mEPSCs in MNCs are independent of external Ca 2ϩ (Inenaga et al, 1998), and since the inhibition of mEPSC frequency persisted when all Ca 2ϩ was removed/buffered, this suggests that the target of inhibition is Figure 5. -Opioid-mediated inhibition does not require presynaptic potassium channels.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, since the frequency of mEPSCs recorded in MNCs is independent of external Ca 2ϩ (Inenaga et al, 1998), we next tested whether the -opioid inhibition of mEPSC frequency persisted in the absence of Ca 2ϩ . To remove Ca 2ϩ , slices were incubated in 0 mM Ca 2ϩ /4 mM Mg 2ϩ , 100 M EGTA, and 50 M BAPTA-AM for 1-2 h. During whole-cell recordings, slices were perfused continually with 0 mM external Ca 2ϩ and 100 M EGTA.…”
Section: Dynorphin Inhibits Evoked Glutamate Neurotransmissionmentioning
confidence: 99%